Identifying an oligometastatic phenotype in HPV-associated oropharyngeal squamous cell cancer: Implications for clinical trial design. (January 2021) - Fleming, Christopher W.; Ward, Matthew C.; Woody, Neil M.; Joshi, Nikhil P.; Greskovich, John F.; Rybicki, Lisa; Xiong, David; Contrera, Kevin; Chute, Deborah J.; Milas, Zvonimir L.; Frenkel, Catherine H.; Brickman, Daniel S.; et al.
Highlights: Patients with metastatic HPV+ SCC-OP may be appropriate candidates for MDT. Trials evaluating the benefit of MDT generally enrich for indolent phenotypes. In our study, patients with 1 metastatic lesion survived 41.2 months after DM. Patients with no smoking history survived 37.6 months after DM. These factors should be used as stratification variables for such clinical trials. Abstract: Objectives: Patients with human papillomavirus (HPV) associated squamous cell carcinoma of the oropharynx (SCC-OP) have improved overall survival (OS) after distant metastasis (DM) compared to HPV negative patients. These patients may be appropriate candidates for enrollment on clinical trials evaluating the efficacy of metastasis-directed therapy (MDT). This study seeks to identify prognostic factors associated with OS after DM, which could serve as enrollment criteria for such trials. Materials and methods: From an IRB approved multi-institutional database, we retrospectively identified patients with HPV/p16 positive SCC-OP diagnosed between 2001 and 2018. Patterns of distant failure were assessed, including number of lesions at diagnosis and sites of involvement. The primary outcome was OS after DM. Prognostic factors for OS after DM were identified with Cox proportional hazards. Stepwise approach was used for multivariable analysis. Results: We identified 621 patients with HPV-associated SCC-OP, of whom 82 (13.2%) were diagnosed with DM. Median OS after DM was 14.6 months. On multivariable analysis, smoking history and number of lesions were significantly associated with prolonged OS. Median OS after DM by smoking (never vs ever) was 37.6 vs 11.2 months (p = 0.006), and by lesion number (1 vs 2–4 vs 5 or more) was 41.2 vs 17.2 vs 10.8 months (p = 0.007). Conclusion: Among patients with newly diagnosed metastatic HPV-associated SCC-OP, lesion number and smoking status were associated with significantly prolonged overall survival. These factors should be incorporated into the design of clinical trials investigating the utility of MDT, with or without systemic therapy, in this population.